Posthumanizing Folklore in the Twenty-First Century: The Case of Matteo Garrone - a Marca, Pablo (Quaderni d'Italianistica, 2025)
This essay explores Matteo Garrone’s Tale of Tales (2015) and Pinocchio (2019) as cinematic retellings of folkloric texts that contribute to critical posthumanist discourse. Garrone’s films are specific performances of fairy tales that, via technology, have a defamiliarizing effect on the relation between human and non-human entities, making the films non-human narrations. Through technical codes and mise-en-scène, Garrone highlights how the human needs to be redefined in relation to the non-human world. Moreover, the films depict hybrid entities whose constructedness is emphasized by special effects with the intent of showing the arbitrariness of ontological categories. This idea, which dominates the entities in Tale of Tales, is expanded upon in Pinocchio, where all animal characters have human faces, inviting an ethical discourse on the treatment of animals. The two films, therefore, are technical performances of the defamiliarizing and, by extension, posthumanist, quality of fairy tales.